Peranan lingkungan kerja dalam menigkatkan motivasi serta dampaknya pada komitmen organisasi karyawan - Zulfikar, Ryandi; Sumiyati, Sumiyati; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2019)
The purpose of the research to find out the influence of work environment toward motivation and motivation effect to organizational commitment. The object which became analysis unit in this research are employees of textile industry X. This research is using verificative with explanatory survey as a method. Data collection technique used questionnaire with 180 respondents as sample. The result of this research found that the influence of work environment toward the motivation is 69,1% which was in the strong category. However, motivation affects to employee organizational commitment is 45,3% which was in the strong category. This research found out that if work environment is conducive, it will increase employee motivation. High motivation will build high organizational commitment. The employees who have high organizational commitment will do the job optimally and more responsible, so that the company could achieve the objectives.